2006
DOI: 10.1007/s00442-005-0337-4
|View full text |Cite
|
Sign up to set email alerts
|

Richness and species composition of arboreal arthropods affected by nutrients and predators: a press experiment

Abstract: A longstanding goal for ecologists is to understand the processes that maintain biological diversity in communities, yet few studies have investigated the combined effects of predators and resources on biodiversity in natural ecosystems. We fertilized nutrient limited plots and excluded insectivorous birds in a randomized block design, and examined the impacts on arthropods associated with the dominant tree in the Hawaiian Islands, Metrosideros polymorpha (Myrtaceae). After 33 months, the species load (per fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 77 publications
5
25
0
1
Order By: Relevance
“…Reduction in richness and diversity mirrored this fire frequency relationship. Thus, we found strong support, as others have (Gruner andTaylor 2006, Hillebrand et al 2007), for increased dominance as the mechanism driving the decline in diversity with herbivore removal.…”
Section: Discussionsupporting
confidence: 87%
“…Reduction in richness and diversity mirrored this fire frequency relationship. Thus, we found strong support, as others have (Gruner andTaylor 2006, Hillebrand et al 2007), for increased dominance as the mechanism driving the decline in diversity with herbivore removal.…”
Section: Discussionsupporting
confidence: 87%
“…Even a short-term increase in a resource that is limiting (a resource pulse) can have extended effects on community structure, trophic interactions and ecosystem function [9]. Although a growing number of studies document the widespread effects of sporadic nutrient or basal-resource pulses on plant productivity and food web structure [5], [7], [9], [10], [11], [12], [13], [14], [15], [16], [17], [18], few have examined how long-term nutrient loading (a resource press) impacts recipient communities [3], [4], [19], [20], and fewer yet have contrasted the food web effects of a nutrient pulse with a press in the same system [3], [21]. In previous work, we found that increased primary production via nitrogen fertilization alters arthropod community structure and composition in Spartina marshes; species richness of herbivores, predators, parasitoids and detritivores all increased in response to nitrogen addition [18].…”
Section: Introductionmentioning
confidence: 99%
“…Not only is insect biodiversity shaped directly by the diversity of plants or their spatial distribution over the landscape (Root 1973, Di Giulio et al 2001, Tscharntke and Brandl 2004, insect diversity is also strongly affected by intraspecific variation in plants Price 1988, Maddox andRoot 1990). This effect of intraspecific variation at the first trophic level may even scale up to the fourth trophic level in insect communities (Bukovinszky et al 2008) and extend to vertebrate predators (Bailey et al 2006, Gruner andTaylor 2006). Therefore, variation in plant traits may significantly influence ecosystem biodiversity (Dungey et al 2000, Hochwender and Fritz 2004, Wimp et al 2005, Poelman et al 2008c (Dungey et al 2000, Johnson and Agrawal 2005, Bangert et al 2006.…”
Section: Introductionmentioning
confidence: 99%